Penerapan Program Fisioterapi Untuk Mengatasi Permasalahan Nyeri Leher Pada Komunitas Pengrajin Stamp Batik Laweyan - Arif Pristianto; Naufal, Adnan Faris; Istiqomah, Istiqomah; Azizah, Ummi (Universitas Muhammadiyah Surakarta, 2023)
Pain in the neck and shoulder area is a common problem that is very complained by the community. Most of the pain points occur in the m. upper trapezius, m. levator scapula, m. infraspinatus and m. scalenus. One of the muscles that is very susceptible to pain is the upper trapezius muscle. One of the jobs that can cause pain in the neck is the batik stamp craftsmen. The process of making batik stamps starts from the neck, shoulders, elbows and hands working in different positions. This position lasts for several hours and is often unknowingly positioning the body is not ergonomic. Functional neck when doing activities with poor ergonomics for a long time causes continuous muscle tension. This can cause muscle contractures, pain and limitation of the scope of motion (LGS) of the neck, thus disrupting the functional activities of the neck. The method used to assess the risk of work attitude using Rapid Entry Body Assessment (REBA) while for pain complaints used Visual Analogue Scale (VAS). The physiotherapy program provided was in the form of stretching exercises with the Integrated Neuromuscular Inhibition Technique (INIT) as well as education related to ergonomic positions. The activities were monitored for 2 weeks there was an increase in workers' understanding of a good position and how to deal with complaints related to neck pain with the techniques taught. Massive information in the form of direct simulations related to stretching movements and the installation of banners related to exercise information as well as consultations via WhatsApp groups and teleconference media proved to be very effective.